Penta carbides: Two-dimensional group-IV semiconductors containing C-2 dimers for nanoelectronics and photocatalytic water splitting - Kilic, Mehmet Emin; Lee, Kwang-Ryeol (AMER PHYSICAL SOC, 2021)
The discovery of novel materials with superior tailored properties is highly attractive for nano- and optoelectronics. Inspired by penta graphene, we introduce a novel family of two-dimensional group-IV materials with C-2 dimers, namely penta carbides. The first-principles calculations reveal that the unitary, binary, and ternary penta carbides have excellent energetic, dynamical, thermal, and mechanical stability with remarkable properties. The unitary penta carbide displays auxetic behavior whereas the binary and ternary penta carbides posses near zero and positive Poisson's ratio. The phonon dispersion curves of penta carbides indicate a remarkable phononic gap, which can be tuned by alloy engineering and hydrogenation. They are semiconductor in nature with band-gap energy ranging from 1.35 and 2.39 eV. Alloying and strain engineering enable the direct modification of atomic bonding and thereby tuning of electronic band gap of penta carbides. Such novel tunable electronic and phononic properties of penta carbides can find applications in the field of nanoelectronics, sensors, and frequency filter applications. The band edge positions of penta carbides (except for Sn-based ones) straddle the redox potentials of water. Remarkably, penta carbides exhibit very high optical absorption in the visible and ultraviolet regions (up to 10(-6) cm(-1)). They have small and anisotropic carrier effective masses, indicating fast carrier transport characteristics and promoting the photo-generated electron-hole separation efficiency. The high specific surface areas, suitable and sizable band gaps, appropriate band edges, small effective carrier masses, and excellent optical absorption capability, all these exotic properties taken together, make penta carbides promising candidates for photocatalytic water splitting.
Keywords: LAYERED SIC SHEETS; ULTRASOFT PSEUDOPOTENTIALS; DYNAMICS; 1ST-PRINCIPLES; SIMULATIONS; MONOLAYERS; GERMANENE; SILICENE; CATALYST; GROWTH